Tajweed’s Nun Sakinah and Tanwin Mobile Guessing Game - Ahmad Ridauddin, Saiful Arieff; Ramle, Rossni; Zailan, Muhammad Amin Fitri; Suhaili, Muhammad Izzat Hanafi (Multidisciplinary Applied Research and Innovation, 2022)
Understanding in Tajweeds is so important to all Muslims as it will be a significant element in prayer and Quran recitation specifically more important to all young Muslims. This paper was proposed a mobile guessing game to assess knowledge of the rules of nun sakinah and tanwin in a fun way. The game was designed using a Game-Based Learning model, developed using Unity and tested by 30 young adult Muslims. The result shows very positive feedback from 30 testers. In conclusion, this application can be a source of knowledge to enhanced young Muslims in their Islamic practice.